DETECTION METHODS, TRANSMISSION AND PATHOGENICITY OF Fusarium spp IN Pinus taeda SEEDS - Silva, Thaisa Wendhausen Ramos da (2017)
The root rots (RR), caused by the Fusarium spp., causes loss of seedling in the nursery that show, initially, discoloration of the needles to a yellowish-green tone followed by apical curvature, wilt and the consequent death of the seedling. The objectives of this work were to: a) define the most appropriate and efficient method to detect Fusarium spp. in Pinus taeda seeds; b) verify if there is transmission of Fusarium spp. from seeds to Pinus taeda seedlings; c) develop a descriptive scale to evaluate the severity of the RR in Pinus taeda seedlings; d) evaluate the pathogenicity, aggressiveness and area under the disease progress curve (AUDPC) of isolated Fusarium subglutinans. For detection three treatments were applied to six lots of Pinus taeda seeds, being four repetitions of 25 seeds: blotter test, paper card and selective medium. The transmission was evaluated in seeds from six lots of Pinus taeda during 60 days counting the percentage of emerged plantlet (EP), non-germinated seeds (NGS) and from NGS seeds with Fusarium spp. A descriptive scale of grades was developed to evaluate the severity of RR in Pinus taeda seedlings. The severity and the incidence of the illness were evaluated at 7, 14, 21 and 28 days after the inoculation from Pinus taeda seedlings of six months of age. The pathogenicity, severity and incidence of twelve isolated Fusarium subglutinans obtained in the detection test. To test for pathogenicity and aggressiveness 13 treatments with 15 replications were applied. The most sensitive detection method to detect Fusarium spp. on Pinus taeda seeds was the selective medium; transmission was not observed of Fusarium spp. from seeds to the seedlings; the descriptive scale allowed evaluating the progression of RR symptoms; nine isolated of Fusarium spp. were found to be pathogenic to Pinus taeda seedlings, reproducing typical symptoms of RR, being isolated L3R2, the most aggressive and that exhibited higher AUDPC.